2010
DOI: 10.1021/ja100399m
|View full text |Cite
|
Sign up to set email alerts
|

Using Isotopic Tools to Dissect and Quantitate Parallel Metabolic Pathways

Abstract: 4-hydroxyacids are ubiquitous in human physiology. They are derived from the drugs of abuse γ-hydroxybutyrate (GHB), γ-hydroxypentanoate(GHP), in addition to the omnipresent lipid peroxidation product 4-Hydroxy-2-(E)-nonenal (4-HNE). Previously we reported that 4-hydroxyacids are catabolized through two parallel pathways. In this report we detail two isotopic tools that have allowed the dissection of this catabolic process, and illustrate how these tools can be used to quantify the relative flux down each path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 23 publications
3
51
0
Order By: Relevance
“…After identifying reactions which should have increased turnover based on changes to substrates, we investigated further evidence of pathway activation from hyperglycemia. Examination of these reactions generally showed increases in amine products (reactions 1,4,5,6,8). In certain cases (reactions 2, 3, and 7), the product was below our limit of detection (LOD) even though they were targeted for analysis.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…After identifying reactions which should have increased turnover based on changes to substrates, we investigated further evidence of pathway activation from hyperglycemia. Examination of these reactions generally showed increases in amine products (reactions 1,4,5,6,8). In certain cases (reactions 2, 3, and 7), the product was below our limit of detection (LOD) even though they were targeted for analysis.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Our interest in levulinate arose from our recent study of the metabolism of 4-hydroxyacids, which are products of lipid peroxidation (C 9 , C 6 ) or drugs of abuse (C 4 , C 5 ) (5,6). We showed that 4-hydroxyacids with 5 or more carbons are metabolized by two new pathways.…”
mentioning
confidence: 99%
“…Tandem mass spectrometry provides information on the fragmentation, which is critical in the identification of new unknown metabolites. For example, the identity of 4-phosphopentanoyl-CoA, a metabolite of 4-hydroxypentanoic acid, is deduced by careful analyzing its fragmentation pattern in positive ionization mode of tandem mass spectrometry Sadhukhan et al, 2010). This example demonstrates the utility of product ion scan for identification of new metabolites.…”
Section: New Metabolite Discovery By Tandem Mass Spectrometrymentioning
confidence: 99%
“…HNE oxidation to 4-hydroxynonanoic acid is another major detoxification pathway. We identified two parallel catabolic pathways of 4-hydroxynonanoic acid in rat liver Sadhukhan et al, 2010). Two pathways are shown in Fig 8. The first round beta oxidation is the same for both pathways.…”
Section: Tandem Mass Spectrometry Combined With the Mass Isotopomer Amentioning
confidence: 99%